2022
DOI: 10.12688/f1000research.51912.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to under-reporting of patient safety incidents in Indonesia: leaders’ perspectives

Abstract: Background: Understanding the causes of patient safety incidents is essential for improving patient safety; therefore, reporting and analysis of these incidents is a key imperative. Despite its implemention more than 15 years ago, the institutionalization of incident reporting in Indonesian hospitals is far from satisfactory. The aim of this study was to analyze the factors responsible for under-reporting of patient safety incidents in Indonesian public hospitals from the perspectives of leaders of hospitals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This finding was consistent with a previous study that found that despite knowing about a reporting system in their hospital, staff did not know how to access an incident form or what to do with it once completed ( 34 ) . A previous study in Indonesia with similar findings highlighted a lack of knowledge and understanding regarding incident reporting ( 14 ) . A previous study identified three crucial phases of incident reporting: awareness and knowledge of the system, the ability to recognize reportable incidents, and the capacity to overcome any reporting barriers ( 35 ) .…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This finding was consistent with a previous study that found that despite knowing about a reporting system in their hospital, staff did not know how to access an incident form or what to do with it once completed ( 34 ) . A previous study in Indonesia with similar findings highlighted a lack of knowledge and understanding regarding incident reporting ( 14 ) . A previous study identified three crucial phases of incident reporting: awareness and knowledge of the system, the ability to recognize reportable incidents, and the capacity to overcome any reporting barriers ( 35 ) .…”
Section: Discussionsupporting
confidence: 52%
“…Fear of being blamed or punished has also been identified as a significant cultural barrier ( 16 , 40 ) . A positive culture is required to raise individuals’ awareness of incident reporting ( 14 ) . Therefore, improving patient safety culture may also improve nurses’ attitudes towards incident reporting ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our data, systematic reporting, going through the incidents in ward meetings, and informing management were such practices. Our positive fnding was that staf is reporting the incidents, which is not always self-evident or daily practice at the hospital level [28]. Fear of consequences and inefective systems are central examples that may cause underreporting of incidents [29].…”
Section: Discussionmentioning
confidence: 94%